Association between Body Mass Index and Bone Mineral Density in Patients Referred for Dual-Energy X-Ray Absorptiometry Scan in Ajman, UAE - Tarek Fawzy; Jayakumary Muttappallymyalil; Jayadevan Sreedharan; Amal Ahmed; Salma Obaid Saeed Alshamsi; Mariyam Saif Salim Humaid Bin Bader Al Ali; Khawla Ahmed Al Balsooshi (Journal of Osteoporosis)
Body Mass Index (BMI) is a good indicator for measurements of Bone Mineral Density (BMD) which measures the density of minerals present in the bones using a special scan. This study was conducted to assess the association between BMI and status of BMD among 101 individuals who underwent Dual-Energy X-ray Absorptiometry (DEXA) scan. 39 subjects had normal and 62 had low bone mineral density. BMD was low in 82.4% of people with normal BMI, 78.1% among overweight, and 44.2% among obese. There was a statistically significant association between these two variables (𝑃<.001). Low BMD was recorded in 59.1% of females and 76.9% of males. Association between advancing age and lower BMI is an important risk factor in the occurrence of low BMD.